Diminished virulence of a sar-/agr- mutant of Staphylococcus aureus in the rabbit model of endocarditis. - Cheung, A L (1994)
Microbial pathogenicity in Staphylococcus aureus is a complex process involving a number of virulence genes that are regulated by global regulatory systems including sar and agr. To evaluate the roles of these two loci in virulence, we constructed sar-/agr- mutants of strains RN6390 and RN450 and compared their phenotypic profiles to the corresponding single sar- and agr- mutants and parents. The secretion of all hemolysins was absent in the sar-/agr- mutants while residual beta-hemolysin activity remained in single agr- mutants. The fibronectin binding capacity was significantly diminished in both single sar- mutants and double mutants when compared with parents while the reduction in fibrinogen binding capacity in the double mutants was modest. In the rabbit endocarditis model, there was a significant decrease in both infectivity rates and intravegetation bacterial densities with the double mutant as compared to the parent (RN6390) at 10(3)-10(6) CFU inocula despite comparable levels of early bacteremia among various challenge groups. Notably, fewer bacteria in the double mutant group adhered to valvular vegetations at 30 min after challenge (10(6) CFU) than the parent group. These studies suggest that both the sar and agr loci are involved in initial valvular adherence, intravegetation persistence and multiplication of S. aureus in endocarditis.